Dengue infection in central India: a 5 years study at a tertiary care hospital - Deshkar, Smita T.; Raut, Sharmila S.; Khadse, Ravindra K. (International Journal of Research in Medical Sciences, 2017)
Background: Dengue is one of the most important mosquito borne viral disease with wide spectrum of clinical presentation and often with unpredictable clinical evolution and outcome. Approximately 50 million infections occur annually world-wide, but what’s the real size of the problem in India? Nobody truly knows...!! Present study was carried out to determine seropositivity, clinical profile and seasonal variation of dengue infection in central India. Methods: Study was carried out from January 2012 to December 2016. Blood samples were collected from 15,606 patients with dengue like clinical illness and serum was separated. All the samples were subjected to IgM antibody detection by dengue MAC ELISA. Results: Prevalence of dengue in dengue suspected cases was found to be 24.49% (3,822/15,606). Maximum number of positive cases, 1,548 (40.50%) were in the age group of 0-10 years. Males (60.83%) were affected more than females (39.17%). Peak was observed in the months of August, September, October and November. Common presenting features were fever followed by myalgia, arthralgia, headache and bleeding manifestations. Significant drop in platelet count was observed in patients with dengue shock syndrome and dengue haemorrhagic fever. Conclusions: Number of dengue cases in central India are on increase and continued surveillance is essential to determine epidemiological and seasonal trend.